REVIEW: QUALITY OF LIFE OF TYPE 2 DIABETES MELLITUS PATIENT WITH APPLICATION OF LIFESTYLE - Yunita, Alfiranty; Aretzy, Alfia (Universitas Muhammadiyah Magelang, 2024)
Diabetes is a chronic disease that has increased growing from year to year in the number of sufferers from year to year. It is associated with changes in lifestyle in modern times that can affect the quality of life of the patients. The quality of life itself refers to the value assigned during a lifetime that changes with decreased functional, perceptual, and social value and can be affected by disease and treatment. The assessment of the quality of life, especially for patients with type 2 diabetes mellitus, aims to restore not only physical function in terms of mobility but also perceptions of health. This research aims to determine the role of lifestyle in improving the quality of life of type 2 diabetes mellitus patients. The non-experimental study is based on a review of various articles on the quality of life of people with type 2 diabetes mellitus published in various national journals from 2016 to 2022. The results of this study showed that exercising, consuming a balanced, nutritious diet, and monthly health check-ups greatly contribute to the improvement of the quality of life. The quality of life can also be measured using the EQ-5D-5L instrument which cover five domains mobility (the ability to move or walk), self-care, usual activities, pain or discomfort, and anxiety or depression and five domain levels. This article concludes that a good lifestyle can improve the quality of life of type 2 diabetes mellitus patients